Application of Carbon Nanotube (CNT) to Improve Mechanical Properties of Concrete: A Comparative Analysis with Superplasticizer - Sunarno, Yohans; Abduh, Natsir; Eka Yuniarto; Tumpu, Miswar; Nelfia, Lisa Oksri (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Many researchers' interest in carbon nanotube (CNT) materials has grown as a result of their potential use in the construction industry. This is mostly related to the mechanical, electrical, thermal, kinetic, and chemical properties of CNT, which have a big impact on the way concrete functions. Hydrated calcium silicate is a complex network of binding particles that compose the cement composite material known as concrete. Since it has nanoscale features, CNT will interact most strongly with hydrated calcium silicate, improving the concrete's mechanical qualities. The purpose of this study is to ascertain the impact of adding CNT to concrete mixtures. Three distinct mixes were created by varying the types and amounts of admixtures that were added to the concrete mix.  Two mixed variations employed CNT at various doses, while one mixed variation used admixture type F (superplasticizer), and the performance of one was compared to the other. Concrete that was both new and hard underwent specimen testing. On fresh concrete, a slump test was conducted using ASTM C163, while for hard concrete, cylindrical specimens measuring 100 mm x 200 mm were tested for unit weight and compressive strength at 7, 14, and 28 days following ASTM C39. According to the test results, utilizing CNT at a lower dose than the typical superplasticizer dose leads to greater workability and compressive strength. The results of the workability and compressive strength tests will be improved by the inclusion of CNT.